Ethnocentrism in foreign policy : can we understand the Third World? - Wiarda, Howard J. (Washington : American Enterprise Institute for Public Policy Research, 1985)
This thesis to addresses foreign policy problems in the Third World, specifically, the argument on dilemmas deeply ingrained in the American foreign policy.
Includes bibliographical references.
sju 23/01/2019
Loans
Keywords: Ethnocentrism; Developing countries; United States; United States